The paradoxical role of stem cells in osteosarcoma: from pathogenesis to therapeutic breakthroughs - Su, Zhengbing; Fang, Xiang; Duan, Hong (Frontiers in Oncology, 2025)
Osteosarcoma (OS), the most prevalent primary malignant bone tumor in adolescents, exhibits a high metastatic potential and resistance to therapy. This characteristic results in a dismal prognosis in advanced cases even following multimodal therapies. This review synthesizes the dual roles of stem cells in OS pathogenesis and therapeutic innovation. Cancer stem cells (CSCs) drive tumor initiation, progression, and chemoresistance through dysregulated molecular pathways that include Wnt/β-catenin, Notch, and Hedgehog signaling, with key markers such as CD133 and CXCR4 contributing to stemness maintenance and metastasis. Concurrently, mesenchymal stem cells (MSCs) paradoxically influence OS progression. Although their tumor-homing capacity enables targeted drug delivery (e.g., IDD-1040-paclitaxel complexes) and immunomodulation, MSC-derived factors like TGF-β can promote cancer-associated fibroblast differentiation and immune evasion. The immunosuppressive tumor microenvironment (TME), characterized by hypoxia-induced HIF-1α activation, metabolic reprogramming, and M2 macrophage polarization, further facilitates CSC resilience and therapy resistance. Emerging strategies—including CSCs-targeted agents (AZD1080, DNMTi/HDACi), CRISPR/Cas9-engineered CD133-directed CAR-T cells, and MSC-mediated delivery of oncolytic viruses—show preclinical promise in overcoming these barriers. However, critical challenges persist: intratumoral CSC heterogeneity limits targeted therapy efficacy; MSC functional plasticity risks tumor promotion via fusion or batch variations; and inefficient cell homing due to pulmonary entrapment reduces therapeutic delivery. Future directions necessitate biomarker-guided combinatorial approaches, optimized MSC administration routes (e.g., intra-arterial injection), and integrated multi-omics profiling to address translational bottlenecks. Resolving these issues will advance personalized stem cell-focused therapies for OS.